5-(2-Hydroxyphenyl)-4-(p-tolyl)-2,4-dihydro-1,2,4-triazole-3-thione - Genç, S; Dege, N; Çetin, A; Cansiz, A; Sekerci, M; Dinçer, M (Int Union Crystallography, 2004)
In the structure of the title compound, C15H13N3OS, the molecules form centrosymmetric dimers through strong N - H ... S hydrogen bonds, with an N - H ... S distance of 3.271 (3) Angstrom. In addition, the molecule contains one O - H ... N intramolecular hydrogen bond. The dimers are connected through weak intermolecular C-H... S hydrogen bonds into chains in the c direction, with a C ... S distance of 3.742 (3) Angstrom.